Basic sciences in higher education, and teaching approaches in the context of 21st-century advances: Time for a change? - Maarman, G. J. (South African Journal of Higher Education, 2023)
Higher education has become a leading life goal for youth across the world. More specifically, the higher education of basic scientists is key in the creation of new developments in economics, healthcare, science, and technology. However, advances and challenges that came with the 21st century have impacted how basic science research is conducted and how basic scientists function within a rapidly changing world. Without a doubt, the way in which basic scientists are trained at higher education institutions needs to be revisited and adapted where needed. By means of a literature review, this article demonstrates the significant challenges and advances in the 21st century, and how these impact the higher education of basic scientists. To summarise, training programmes must include a digitalisation focus and teach the use of digital technology to disseminate research findings to the lay public. Training must hone the skills that will help scientists to survive job scarcity in academia, skills such as curriculum vitae writing, promoting oneself as employable to industry companies and how to repurpose academic experiences for a different job market. Other aspects that need to be included are raising awareness, among the next generation of basic scientists, of the need to conduct research that has nationally and internationally relevant foci. Training must include mentorship during postgraduate training, the use of hybrid models of teaching, curricular integration and interdisciplinary learning and practices during the early stages of these scientists’ careers. Lastly, undergraduate degrees give a general introduction to the basic sciences, but leave graduates with insufficient laboratory experience, and thus they struggle to enter the job market after their undergraduate degree is completed. In other fields, a B. in Accounting makes a graduate an accountant, B. Eng makes them an engineer, but BSc. equates to nothing besides several introductions to various fields. More must be done.